2010
DOI: 10.1136/adc.2009.180695
|View full text |Cite
|
Sign up to set email alerts
|

Parental comprehension and satisfaction in informed consent in paediatric clinical trials: a prospective study on childhood leukaemia

Abstract: The parents signed consent forms without having fully understood all the elements specific to the experimental protocol. Rather, the parents based their decision on their confidence in the medical team, even when their child's life was at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 20 publications
3
58
1
3
Order By: Relevance
“…Thus we did not perform sample size calculation, and anticipated that approximately 100 respondents would allow us to achieve our goal [8,9]. Please see electronic supplementary material for a list of factors which we anticipated may be associated with consent provision and refusal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we did not perform sample size calculation, and anticipated that approximately 100 respondents would allow us to achieve our goal [8,9]. Please see electronic supplementary material for a list of factors which we anticipated may be associated with consent provision and refusal.…”
Section: Discussionmentioning
confidence: 99%
“…A French survey of 76 SDMs of critically ill adult patients revealed that more than half failed to understand information presented to them regarding clinical diagnosis, prognosis, or treatment [8]. Chappuy et al [9] reported similar poor comprehension in parents whose consent was sought for their child to participate in a therapeutic leukemia trial: half could explain neither the aim of the research nor the potential benefit of inclusion to their child. There is also evidence that research decision-making is burdensome, as Azoulay et al [12] found that being asked to provide consent for research was associated with posttraumatic stress symptoms in 35% of family members of critically ill patients, compared with less than 10% in those involved in decisions about clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Especially mothers tend to refrain from a clear distinction between discussing possible participation in clinical trial and discussing their child's treatment options. As a result, treatment and research appear inseparable to mothers of children participating in a clinical trial [37,39]. In the decision-making process, parents potentially fail to grasp the distinction between the imperatives of clinical research and of ordinary treatment.…”
Section: Parent's Comprehensionmentioning
confidence: 99%
“…Many parents were not aware at the time of giving consent that they can refuse participation or withdraw from the study at any time without negative consequences for their child [13,19,39]. Several studies [48,49] reported that between 45% and 80% of parents understood that they can withdraw their child from the ongoing study.…”
Section: Parent's Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation